Emerging Concepts in the Resolution of Periodontal Inflammation: A Role for Resolvin E1 - Balta, Maria G.; Loos, Bruno G.; Nicu, Elena A. (Frontiers in Immunology, 2017)
Inflammatory response is a protective biological process aimed to eliminate the harmful effect of the insulting influx. Resolution of inflammation constitutes an active sequence of overlapping events mediated by specialized proresolving mediators i.e. lipoxins, resolvins, protectins and maresins originating from the enzymatic conversion of poly unsaturated fatty acids (PUFAs). Unresolved acute inflammatory response results in chronic inflammation, a leading cause of several common pathological conditions. Periodontitis is a biofilm-induced chronic inflammatory disease, which results in loss of periodontal connective tissue and alveolar bone support around the teeth, leading to tooth exfoliation. An inadequate proresolving host response may constitute a potential mechanism explaining the pathogenesis of periodontal disease. An emerging body of clinical and experimental evidence has focused on the underlying molecular mechanisms of resolvins and particularly Resolvin E1 (RvE1) in periodontitis. Recently, RvE1 has been directly correlated to the resolution of inflammation in periodontal disease. Herein, we provide a comprehensive overview of the literature regarding the role and possible mechanisms of action of RvE1 on different cell populations recruited in periodontal inflammation as well as its potential therapeutic implications. Along with recent data on the benefits of PUFAs supplementation in periodontal clinical parameters, we touch upon suggested future directions for research.